Correcting the reward imbalance in binge eating: A pilot randomized trial of reward re-training treatment. (1st September 2022) - Juarascio, Adrienne S.; Presseller, Emily K.; Wilkinson, Megan L.; Kelkar, Apoorva; Srivastava, Paakhi; Chen, Joanna Y.; Dengler, Julia; Manasse, Stephanie M.; Medaglia, John
Abstract: Behavioral treatments for psychological disorders characterized by reward-driven maladaptive behaviors (e.g., substance use disorder, eating disorders, behavioral addictions) primarily seek to reduce hyper-reward response to disorder-specific stimuli. Suboptimal outcomes for these treatments highlight the need to also target hypo-reward response to day-to-day life activities. The present study sought to conduct an initial test of a novel behavioral treatment, Reward Re-Training (RRT) to target hyper- and hypo-reward response in individuals with binge eating. Individuals with binge eating ( N  = 23) were randomly assigned to either 10 weeks of outpatient, group-based RRT treatment or a waitlist control. RRT was found to be feasible and acceptable, demonstrated large impacts on both hypo- and hyper-reward response (measured by self-report (pre-to post-treatment ηp 2 range 0.38–0.58) and neural activation via fMRI), and was efficacious in reducing eating disorder pathology (ηp 2 range 0.40–0.64, including binge eating, ηp 2  = 0.64) compared to waitlist control (ηp 2 range 0.00–0.04). This pilot data provides preliminary support for the feasibility, acceptability, and effectiveness of a novel treatment targeting reward imbalance for individuals with binge eating. Future evaluations of RRT may benefit from an active treatment comparison condition and a follow-up assessment to examine persistence of positive outcomes.